Modifying laboratory testing via home brew during the COVID-19 pandemic. Issue 1 (25th January 2021) - Moran, Jeffery H.; Kessler, Larry; Moylan, Jennifer; Forrest, Craig; Boehme, Karl; Kennedy, Josh; Greninger, Alex; Baird, Geoff; Olgaard, Ericka; James, Laura
Abstract: Rapid development and deployment of diagnostic testing for COVID-19 have been a key component of the public health response to the pandemic. Out of necessity, academic and other clinical laboratories developed laboratory testing innovations for COVID-19 to meet clinical testing demands. In addition to constraints on local testing supplies and equipment, a rapidly changing regulatory framework created challenges for translational scientists. Illustrative examples of approaches used to develop laboratory tests during the early stages of the COVID-19 pandemic demonstrate effective team science approaches to this challenging clinical care and public health emergency. These experiences and the associated lessons learned are relevant to the development of public health response plans for future pandemics.